Perspectivas teóricas e históricas das diretrizes legais da Educação Infantil do campo: implicações no contexto amazônico de Parintins - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The Education of the Field is a conception of education that is built on the political fights for the right to land and agrarian reform, specific policies for the territory of the field and its people. In view of this, there emerges the desire for a meaningful education based on the experiences of the people of the field, of the waters, and of the forests, in this process, the multiple realities that exist in the Amazon. The present work proposed to investigate what are the perspectives and limits of the legal guidelines for early childhood education in the field in the Amazonian context of Parintins? Having as problem the following question: What are the perspectives and limits of the legal guidelines for early childhood education in the field in the Amazonian context of Parintins? This is a theoretical research of bibliographic and documental nature, we opted for the Historical Materialism - Dialectic as a method of analysis and theory capable of understanding reality in its multiple dimensions. This research has as a general objective: To investigate the perspectives and limits of the legal guidelines for early childhood education in the field in the Amazonian context of Parintins. And the following objectives:1) To know the theoretical and historical perspectives about early childhood education in the field, 2) To explain and analyze the main normative guidelines of early childhood education in the field, 3) To evaluate the implication of the guidelines in the Amazonian context of the Municipality of Parintins. This study is organized in the following chapters: first, we will deal with the theoretical, historical and political perspectives in relation to Field Education and Early Childhood Education in the Field, and in the second moment we will have the implications of the guidelines in the Amazonian context of Parintins. The theoretical field is anchored in the studies of Arroyo, Caldart and Molina (2011), Arroyo (2007, 2012, 2013), Molina and Rocha-Antunes (2014), Silva (2017), Ghedin (2012), Pojo (2014), Vasconcelos (2016), Benatti (2016), Hage (2015), Kramer (1997), Sacristán (2013), Saul (2009), Freire (1987, 2000,1994) among others, and by studies of authors who address early childhood education among them: Kuhlmann (1998), Pasuch and Silva (2012). So, the paths are given, are legal, but require political will of managers of the executive, legislative and secretary of education of the municipality in reorienting the curriculum proposal for early childhood education in the field, in which the field education is treated in the difference when equality denies and silences their knowledge of the production of life and is treated with equality when the difference makes it inferior.

La Educación del Campo es un concepto de educación que se construye a partir de las luchas políticas por el derecho a la tierra y la reforma agraria, políticas específicas para el territorio del campo y su gente. Por lo tanto, surge el deseo de una educación significativa basada en las experiencias de la gente del campo, de las aguas y de los bosques, en este proceso, las múltiples realidades que existen en la Amazonía. Este trabajo se propuso investigar ¿cuáles son las perspectivas y los límites de las directrices legales para la educación de la primera infancia en el campo en el contexto amazónico de Parintins? Teniendo como problema la siguiente pregunta: ¿Cuáles son las perspectivas y los límites de las directrices legales para la educación de la primera infancia en el campo en el contexto amazónico de Parintins? Se trata de una investigación teórica de carácter bibliográfico y documental, optamos por el Materialismo Histórico - Dialéctico como método de análisis y teoría capaz de comprender la realidad en sus múltiples dimensiones. Esta investigación tiene como objetivo general: Investigar cuáles son las perspectivas y los límites de las directrices legales para la educación de la primera infancia en el campo en el contexto amazónico de Parintins. Y los siguientes objetivos: 1) Conocer las perspectivas teóricas e históricas sobre la educación infantil en el campo, 2) Explicar y analizar las principales directrices normativas de la educación infantil en el campo, 3) Evaluar la implicación de las directrices en el contexto amazónico del Municipio de Parintins. Este estudio está organizado con los siguientes capítulos, en primer lugar se abordarán las perspectivas teóricas, históricas y políticas en relación con la Educación en el Campo y la Educación Infantil en el Campo, ya en el segundo momento tendremos las implicaciones de las directrices en el contexto amazónico de Parintins. El campo teórico está anclado en los estudios de Arroyo, Caldart y Molina (2011), Arroyo (2007, 2012, 2013), Molina y Rocha-Antunes (2014), Silva (2017), Ghedin (2012), Pojo (2014), Vasconcelos (2016), Benatti (2016), Hage (2015), Kramer (1997), Sacristán (2013), Saul (2009), Freire (1987, 2000,1994) entre otros, y por estudios de autores que abordan la educación infantil entre ellos: Kuhlmann (1998), Pasuch y Silva (2012). Por lo tanto, los caminos están dados, son legales, pero requieren la voluntad política de los gestores del ejecutivo, legislativo y secretario de educación del municipio en la reorientación de la propuesta curricular para la educación de la primera infancia en el campo, en el que la educación de campo se trata en la diferencia cuando la igualdad niega y silencia su conocimiento de la producción de la vida y se trata con igualdad cuando la diferencia hace que sea inferior.
Keywords: .; .; .; CIENCIAS HUMANAS; Educação do Campo; Educação Infantil; Contexto Amazônico